Цифровізація освітньо-наукового простору : методичні рекомендації до проведення семінарських занять та організації самостійної роботи здобувачів третього (освітньо-наукового) рівня вищої освіти зі спеціальності 011 «Освітні, педагогічні науки» - Ткачова, Наталія Олександрівна; Ткачов, Артем Сергійович; Байдала, Вікторія Вікторівна; Махновський, Сергій Сергійович; Tkachova, Nataliia Oleksandrivna; Tkachov, Artem; Baidala, Viktoriia; Makhnovskyi, Serhii (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
Методичні рекомендації до навчального модуля «Цифровізація освітньо-наукового простору» як складника інтегрованого навчального курсу «Основи освітньої інноватики. Медіаосвіта. Цифровізація освітньо-наукового простору» містять навчальні й дидактичні матеріали для проведення семінарських занять та організації самостійної роботи здобувачів третього (освітньо-наукового) рівня вищої освіти зі спеціальності 011 Освітні, педагогічні науки.

Methodical recommendations for the module ‘Digitalisation of the Educational and Scientific Space’ as a component of the integrated course ‘Fundamentals of Educational Innovation. Media Education. Digitalisation of the Educational and Scientific Space’ contain educational and didactic materials for conducting seminars and organising independent work of applicants for the third (educational and scientific) level of higher education in the speciality 011 Educational, Pedagogical Sciences.
Digitalisation of the educational and scientific space: methodical recommendations for conducting seminars and organising independent work of applicants for the third (educational and scientific) level of higher education in the speciality 011 Educational, pedagogical sciences
Keywords: SOCIAL SCIENCES::Social sciences::Education; цифровізація; освітньо-науковий простір; цифрові технології; цифрові інструменти; цифрова компетентність; педагог; digitalisation; educational and scientific space; digital technologies; digital tools; digital competence; teacher